Comparison of effects of the tacrolimus and cyclosporine A on the colon anastomosis recovery of rats - Uysal, Erdal (Ann Surg Treat Res, 2017)
PURPOSE: This study aims to examine and compare the effects of immunosuppressant cyclosporine A (CsA) and tacrolimus (TAC) on colon anastomosis recovery. METHODS: Forty rats were randomly divided into 4 groups. The 4 groups were determined as follows: control group; sham group, given %0.09 NaCl; TAC group, given 0.5 mg/kg/day tacrolimus; and CsA group, given 5 mg/kg/day CsA. A 6-cm midabdomen incision was performed on the rats. An incision of all layers on the right colon was performed. Then anastomosis was undertaken. Laparotomy was performed on the seventh day postoperation. The colon bursting pressures were evaluated, histopathological examinations were undertaken, and E-cadherin expression and tissue hydroxyproline levels were evaluated. RESULTS: Statistically significant differences were observed among bursting pressures of the groups (P < 0.001). The value was significantly low in TAC and CsA groups when compared to control and sham groups (P < 0.05). The tissue hydroxyproline levels were significantly low in TAC group compared to control group (P = 0.03). Fibroblast density and neovascularization were significantly greater in the control group compared to the TAC group (P < 0.05). Levels of collagen had decreased significantly in TAC group compared to other groups (P < 0.05). CONCLUSION: Our study showed that TAC may have a negative effect of colon anastomosis recovery. The lowest anastomosis bursting pressure was detected in TAC group. Also, collagen, hydroxyproline, fibroblast, neovascularization and E-Cadherin levels were comparatively lower in TAC group. CsA did not cause any significant changes to tissue hydroxyproline, collagen, fibroblast, and E-Cadherin levels.